Prediction and Correlations of Residual Entropy of Superheated Vapor for Pure Compounds - O. Abdullah, Mahmoud; T. Najim, Sarmad; Z. Atta, Shahad (Iraqi Journal of Chemical and Petroleum Engineering, 2012)
Prediction of accurate values of residual entropy (SR) is necessary step for thecalculation of the entropy. In this paper, different equations of state were tested for theavailable 2791 experimental data points of 20 pure superheated vapor compounds (14pure nonpolar compounds + 6 pure polar compounds). The Average AbsoluteDeviation (AAD) for SR of 2791 experimental data points of the all 20 purecompounds (nonpolar and polar) when using equations of Lee-Kesler, Peng-Robinson, Virial truncated to second and to third terms, and Soave-Redlich-Kwongwere 4.0591, 4.5849, 4.9686, 5.0350, and 4.3084 J/mol.K respectively. It was foundfrom these results that the Lee-Kesler equation was the best (more accurate) onecompared with the others, but this equation is sometimes not very preferable. It wasnoted that SRK equation was the closest one in its accuracy to that of the Lee-Keslerequation in calculating the residual entropy SR of superheated vapor, but it wasdeveloped primarily for calculating vapor-liquid equilibrium and to overcome thisproblem, efforts were directed toward the possibility of modifying SRK equation toincrease its accuracy in predicting the residual entropy as much as possible. Themodification was made by redefining the parameter α in SRK equation to be afunction of reduced pressure, acentric factor, and polarity factor for polar compoundsin addition to be originally function of reduced temperature and n parameter –which isalso function of acentric factor– by using statistical methods. This correlation is asfollows:α =[1+n(γ)]2  , γ=-0.920338Pr-0.34091 +0.064049Tr4 ω +0.370002ω-Pr0.996932 Tr-4xThis new modified correlation decreases the deviations in the results obtained byusing SRK equation in calculating SR when comparing with the experimental data.The AAD for 2791 experimental data points of 20 pure compounds is 4.3084 J/mol.Kwhile it becomes 2.4621 J/mol.K after modification. Thus SRK equation after thismodification gives more accurate results for residual entropy of superheated vapor ofpure 20 compounds than the rest of the equations mentioned above.